Acute hemodynamic effects of riociguat in patients with pulmonary hypertension associated with diastolic heart failure (DILATE-1): a randomized, double-blind, placebo-controlled, single-dose study - Bonderman, Diana; Pretsch, Ingrid; Steringer-Mascherbauer, Regina; Jansa, Pavel; Rosenkranz, Stephan; Tufaro, Caroline; Bojic, Andja; Lam, Carolyn S P; Frey, Reiner; Ochan Kilama, Michael; Unger, Sigrun; Roessig, Lothar; et al. (Chest, 2014)
BACKGROUND: Deficient nitric oxide-soluble guanylate cyclase-cyclic guanosine monophosphate signaling results from endothelial dysfunction and may underlie impaired cardiac relaxation in patients with heart failure with preserved left ventricular ejection fraction (HFpEF) and pulmonary hypertension (PH). The acute hemodynamic effects of riociguat, a novel soluble guanylate cyclase stimulator, were characterized in patients with PH and HFpEF. METHODS: Clinically stable patients receiving standard HF therapy with a left ventricular ejection fraction > 50%, mean pulmonary artery pressure (mPAP) ≥ 25 mm Hg, and pulmonary arterial wedge pressure (PAWP) > 15 mm Hg at rest were randomized to single oral doses of placebo or riociguat (0.5, 1, or 2 mg). The primary efficacy variable was the peak decrease in mPAP from baseline up to 6 h. Secondary outcomes included hemodynamic and echocardiographic parameters, safety, and pharmacokinetics. RESULTS: There was no significant change in peak decrease in mPAP with riociguat 2 mg (n = 10) vs placebo (n = 11, P = .6). However, riociguat 2 mg significantly increased stroke volume (+9 mL [95% CI, 0.4-17]; P = .04) and decreased systolic BP (-12 mm Hg [95% CI, -22 to -1]; P = .03) and right ventricular end-diastolic area (-5.6 cm2 [95% CI, -11 to -0.3]; P = .04), without significantly changing heart rate, PAWP, transpulmonary pressure gradient, or pulmonary vascular resistance. Riociguat was well tolerated. CONCLUSIONS: In patients with HFpEF and PH, riociguat was well tolerated, had no significant effect on mPAP, and improved exploratory hemodynamic and echocardiographic parameters. TRIAL REGISTRY: ClinicalTrials.gov; No.: NCT01172756; URL: www.clinicaltrials.gov.
Keywords: senioři; dvojitá slepá metoda; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; senioři nad 80 let; Double-Blind Method; diastolické srdeční selhání; echokardiografie; Retrospective Studies; výsledek terapie; Echocardiography; Hypertension, Pulmonary; Middle Aged; mužské pohlaví; Heart Failure, Diastolic; aplikace orální; srdeční komory; Pyrimidines; pyrimidiny; Follow-Up Studies; následné studie; Aged, 80 and over; Pyrazoles; ženské pohlaví; plicní hypertenze; retrospektivní studie; Humans; Hemodynamics; hemodynamika; Heart Ventricles; lidé středního věku; Administration, Oral; pyrazoly; Female; Aged; Treatment Outcome; lidé; Male